2010
DOI: 10.1186/1472-6947-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prototype clinical decision support tool for osteoporosis disease management: a qualitative study of focus groups

Abstract: BackgroundOsteoporosis affects over 200 million people worldwide, and represents a significant cost burden. Although guidelines are available for best practice in osteoporosis, evidence indicates that patients are not receiving appropriate diagnostic testing or treatment according to guidelines. The use of clinical decision support systems (CDSSs) may be one solution because they can facilitate knowledge translation by providing high-quality evidence at the point of care. Findings from a systematic review of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Physicians in our study reported the same main reasons for not using FRAX as family physicians and general internists in a previous study [30], including poor access to clinical decision support systems. Decision support tools need to be easily accessible and user-friendly to achieve their intended level of use [31].…”
Section: Discussionsupporting
confidence: 60%
“…Physicians in our study reported the same main reasons for not using FRAX as family physicians and general internists in a previous study [30], including poor access to clinical decision support systems. Decision support tools need to be easily accessible and user-friendly to achieve their intended level of use [31].…”
Section: Discussionsupporting
confidence: 60%
“…As part of prototype development of a clinical decision support system for an osteoporosis screening tool, focus groups with general practitioners were conducted in Canada [60]. Practitioners expressed concerns about patients' understanding; technological and time, resources, and process issues [60]. Furthermore, there were concerns that osteoporosis screening might disrupt the actual intended reason for the visit.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the tool development process considered not only empirical evidence to build the prototype but also relied on input from a multidisciplinary group of experts (e.g., human factors' engineers, health information technologists, knowledge translation experts, and osteoporosis specialists). Secondly, both frameworks were used to guide the selection of knowledge relevant to osteoporosis disease management (i.e., systematic review [32]), and to ensure that all tool development studies (i.e., focus groups, and usability studies) were appropriately and rigorously conducted [33,39]. We tested the usability of all three components of the osteoporosis tool (with relevant end users) with as many cycles of iterations as was needed to eliminate problems and errors [39].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a qualitative study of focus groups with family physicians and general internists to obtain their perceptions about clinical decision support systems, and to identify the components of the osteoporosis tool [33]. These findings were then used to transform the conceptual design into a functional, multicomponent prototype tool consisting of three components (see Appendix A at www.jclinepi.com): …”
Section: Phase 3dassess the Barriers And Facilitators To Using The Knmentioning
confidence: 99%